Un enclos funéraire monumental à Langres/Andemantunnum (Haute-Marne) - Yvan Maligorne; Serge Février; Jean-Noël Castorio (Gallia)
The study of thirty-three architectural blocks reused in the fortified wall of Langres, and with similar technical and stylistic characteristics, allows for the restitution of a long monumental facade. The latter is formed by arches decorated with mythological reliefs and framed by pilasters supporting a horizontal entablature. The study of the remains and the inscription on the frieze, as well as the comparative record, indicate that this structure is a monumental tomb, and more specifically a funerary enclosure, which can be dated to the 2nd c. AD, based on the analysis of the architectural ornamentation.